Animal Stories and Oral History: Witnessing and Mourning across the Species Divide. (1st August 2018) - Hamilton, Carrie
Abstract: This article brings oral history into conversation with animal studies. It does so through an analysis of the themes of witnessing and mourning in a life story interview with an early Spanish animal welfare activist. I argue that this interview, which revolves largely around the interrelated processes of witnessing and mourning animal and human lives, provides a lens through which to view the diversity of human-animal relations in one life story. In addition to reviewing some of the existing literature on animals in oral history, the article draws on a range of current discussions in animal studies by such thinkers as Colin Jerolmack, Donna Haraway, Chloë Taylor, and Alice Kuzniar. Through this transdisciplinary approach, the article encourages oral historians to be more attentive to other-than-human animals in their research and demonstrates that oral history can contribute valuable evidence about animal lives and human-animal relations to the emerging field of animal history.